Tren Inovasi Hijau dan Transformasi Digital dalam Mendorong Kinerja UKM: Studi Bibliometrik pada Tata Kelola dan Pembangunan Berkelanjutan di Indonesia - Fitri Wahyuningsih; Masiyah Kholmi (CV. Creative Tugu Pena, 2024)
This study aims to conduct a bibliometric analysis of the literature related to various variables that influence the development of digital transformation and green innovation in the context of sustainable development, with a focus on SMEs, companies, and employees in Indonesia. Through the application of bibliometric analysis methods, this study explores the relationship between concepts such as the role of moderation and mediation, technology integration, green behavior, and related factors such as foreign ownership, openness, governance, and participation in the innovation process. This analysis also investigates the association between countries involved in digital innovation and sustainability, and the role of the medium used by organizations to connect investors and stakeholders. The findings of this study are expected to provide insight into the relationship between these variables and how they support or hinder the implementation of green practices and digital technology in the Indonesian SME sector, as well as their contribution to achieving sustainable development goals. The results of this analysis are also expected to provide a basis for policies and strategies for companies, investors, and the government in creating a more inclusive and sustainable ecosystem.